Pulling Back the Blue Curtain: A Pelagic Monitoring Program for the Blue Belt - Meeuwig, Jessica Jane; Thompson, Christopher David Harburn; Forrest, John Andrew; Christ, Hanna Jabour; Letessier, Tom Bech; Meeuwig, Dirk Jason (Frontiers in Marine Science, 2021)
Ocean health is fundamental to human prosperity. However, fisheries exploitation, industrialisation and climate change imperil our oceans. Marine protected areas (MPAs) have been established in coastal habitats since the 1970s and the ongoing monitoring of these MPAs has clearly shown their ecological and economic value. Demonstrable benefits include biodiversity conservation, fisheries enhancement and climate resilience. Since the 2000s, large scale MPAs (LSMPAs) are increasingly being established, with new parks including extensive areas of pelagic habitat. Seminal was the British Indian Ocean Territory (BIOT) MPA created in 2010. In 2016, the UK Government established the Blue Belt Programme to provide long-term protection of the marine environment across the UK Overseas Territories and LSMPAs have now been established or designated in a number of these territories. Critics argue that MPAs are an ineffective strategy for pelagic species and will not effectively deliver conservation outcomes. This same argument was made for demersal species in the 1970s and evidentially failed. Empirical data for the Blue Belt LSMPAs are needed to demonstrate their effectiveness in conserving pelagic species and to allow managers to monitor and assess the LSMPAs based on the best evidence available. This perspective presents current advances in video-based monitoring of pelagic wildlife and provides examples of key ecological insights gained from their use relevant to LSMPA planning and management. We present a case study from the BIOT MPA and finally, generalise with respect to key learnings that will support planning and monitoring of LSMPAs within the Blue Belt Programme.